IL-6/STAT3 Is a Promising Therapeutic Target for Hepatocellular Carcinoma - Xu, Junnv; Lin, Haifeng; Wu, Gang; Zhu, Mingyue; Li, Mengsen (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is a common malignant tumor of which the occurrence and development, the tumorigenicity of HCC is involving in multistep and multifactor interactions. Interleukin-6 (IL-6), a multifunctional inflammatory cytokine, has increased expression in HCC patients and is closely related to the occurrence of HCC and prognosis. IL-6 plays a role by binding to the IL-6 receptor (IL-6R) and then triggering the Janus kinase (JAK) associated with the receptor, stimulating phosphorylation and activating signal transducer and activator of transcription 3 (STAT3) to initiate downstream signals, participating in the processes of anti-apoptosis, angiogenesis, proliferation, invasion, metastasis, and drug resistance of cancer cells. IL-6/STAT3 signal axes elicit an immunosuppressive in tumor microenvironment, it is important to therapy HCC by blocking the IL-6/STAT3 signaling pathway. Recent, some inhibitors of IL-6/STAT3 have been development, such as S31-201 or IL-6 neutralizing monoclonal antibody (IL-6 mAb), Madindoline A (Inhibits the dimerization of IL-6/IL-6R/gpl30 trimeric complexes), C188-9 and Curcumin (Inhibits STAT3 phosphorylation), etc. for treatment of cancers. Overall, consideration of the IL-6/STAT3 signaling pathway, and its role in the carcinogenesis and progression of HCC will contribute to the development of potential drugs for targeting treatment of liver cancer.